Mental disorders in antiphospholipid syndrome patients: association with clinical and immunological manifestations of the disease - А. В. Borisova; Т. А. Lisitsyna; D. Yu. Veltishchev; Т. М. Reshetnyak; О. F. Seravina; О. В. Kovalevskaya; F. А. Cheldieva; А. А. Abramkin; А. Е. Zeltyn; Е. L. Nasonov (Научно-практическая ревматология)
The aim of this work is to clarify the association between the clinical and psychopathological features of mental disorders (MD) and the clinical and immunological features of antiphospholipid syndrome (APS).Material and methods. The study included 107 patients (34 (31.8%) men and 73 (68.2%) women) aged 18 to 69 years (40.6±10.4 years (M±SD)), 54 (50.5%) – with primary APS (PAPS), established according to the international criteria of 2006 and 53 (49.5%) patients – with reliable diagnosis of systemic lupus erythematosus (SLE), according to the European Alliance of Associations for Rheumatology/American College of Rheumatology (EULAR/ ACR) 2019 criteria, with a secondary APS. Risk of thrombosis in APS was assessed by the GAPSS (Global Anti-Phospholipid Syndrome Score). MD were diagnosed by a psychiatrist in accordance with 10th revision of the International Statistical Classification of Diseases and Related Health Problems (ICD-10) and Diagnostic and Statistical Manual of mental disorders, 5th edition (DSM-5).Results. Mental disorders are detected in the vast majority of patients with APS (98 (91.6%)), predominantly in anxiety-depressive spectrum disorders (ADSD; 90 (84.1%)). Depressive disorders are not associated with a high risk of thrombosis according to the GAPSS, but more severe variants of depression are more common in patients with high anti-β2 -glycoprotein I (anti-β2 GP1) and low/moderate anti cardiolipin (aCL) antibodies. Anxiety disorders were diagnosed only in patients with a high risk of thrombosis according to GAPSS, high aCL and IgG anti-β2 GP1. Schizotypal disorder was identified only in patients with a high risk of thrombosis and positive anti-phosphatidylserine/prothrombin complex antibodies (aPS/PT) regardless of class, and also more often in patients with high IgG anti-β2 GP1. Epilepsy was observed only in patients with positive aPS/PT, regardless of class. Cognitive impairment (CI), mostly mild and moderate, was found in the vast majority of patients with APS (102 (95.3%)). Dementia was detected in 7 (6.5%) patients, and only in those who had acute or transient cerebrovascular accident. When compared with the general population, dementia developed at an earlier age (up to 65 years). For patients with a high risk of thrombosis, moderate CI is more typical. CI and their severity are not associated with the duration of APS, but are associated with positivity for IgG aPS/PT, acute or transient cerebrovascular accident and the duration of comorbid ADSD.Conclusion. A high frequency of MD in patients with APS revealed. Associations of MD with clinical and immunological manifestations of APS were determined. CI in patients with APS is heterogeneous and are associated with both clinical and immunological manifestations of APS and MD. Identification of CI and determination of their characteristics should be confirmed by clinical, psychopathological and pathopsychological methods in order to personalize their correction within the partnership model of care.